Step-by-step explanation:
The sum of ages of two friends is 13 years.
The product of their ages is 42.
<em>Let the age of 1st friend and 2nd friend is x, y respectively.</em>
<em>1 st condition= The sum of ages of two friends is 13 y</em><em>r</em><em>s. </em>
i.e x+y = 13........ (I)
<em>2nd condition= The product of their ages is 42.</em>
i.e X*y = 42........(ii)
From equation (I)
X+y = 13
or, X = 13-y........ (iii)
<em>Putting the equation (iii) in equation (ii).</em>
X*y= 42
(13-y) * y = 42
13y - y^2 = 42
![{y}^{2} - 13y + 42 = 0](https://tex.z-dn.net/?f=%20%7By%7D%5E%7B2%7D%20%20-%2013y%20%2B%2042%20%3D%200)
![{y}^{2} - (7 + 6)y + 42= 0](https://tex.z-dn.net/?f=%20%7By%7D%5E%7B2%7D%20%20%20-%20%287%20%2B%206%29y%20%2B%2042%3D%200)
![{y}^{2} - 7y - 6y + 42 = 0](https://tex.z-dn.net/?f=%20%7By%7D%5E%7B2%7D%20%20-%207y%20-%206y%20%2B%2042%20%3D%200)
![y(y - 7) - 6(y - 7) = 0](https://tex.z-dn.net/?f=y%28y%20-%207%29%20-%206%28y%20-%207%29%20%3D%200)
![(y - 6) (y - 7) = 0](https://tex.z-dn.net/?f=%28y%20-%206%29%20%28y%20-%207%29%20%3D%200)
Either; y-6 = 0
y = 6
Or;
y-7=0
y = 7
<em>Keeping the value of y as "7" in equation (ii)</em>
x*y = 42
7x = 42
X = 42/7
Therefore, the value of X is 6.
Therefore, either 1st friend is 6 years and 2nd is 7 years.
<em><u>H</u></em><em><u>o</u></em><em><u>p</u></em><em><u>e</u></em><em><u> </u></em><em><u>it </u></em><em><u>helps</u></em><em><u>.</u></em><em><u>.</u></em><em><u>.</u></em>
First find the area of the circle then divide it by 4
Answer:
Loggerhead turtles live and migrate around the Atlantic Ocean. Which of the following is an adaptation of Loggerhead turtles? *
Step-by-step explanation:
hi sup
Answer:
y = 40
Step-by-step explanation:
Lets make an equation to represent the sum of the angles:
We know that the sum of angles of triangles equals 180 degrees. So based on this knowledge, the equation is :
2y + y + 10 + 50 = 180
Now we simplify:
2y + y = 3y
10 + 50 = 60
So our new equation is 3y + 60 = 180
Now all we have to do is simplify:
3y + 60 = 180
3y + 60 -60 = 180 - 60
3y = 120
3y / 3 = 120 / 3
y = 40
So the answer is 40 hope this helped